Aiming at a Moving Target: Theoretical and Methodological Considerations in the Study of Intraindividual Goal Conflict between Personal Goals - Gorges, Julia; Grund, Axel (Frontiers in Psychology, 2017)
Multiple-goal pursuit and conflict between personal life-defining goals can be considered part of everyday business in most individuals’ lives. Given the potentially detrimental effects of goal conflict—for example, impaired well-being or poor performance—the literature on goal conflict is surprisingly scattered due to heterogeneous methodological approaches and technical terms. Little empirical research has addressed the conceptualization of goal conflict against the background of differing understandings from a structure-like and a process-like perspective. In the present article, we outline theoretical foundations of goal conflict from two perspectives: a structure- and a process-like perspective. Based on a comparative analysis and integration of these two perspectives, we systematically review empirical studies on goal conflict over 30 years of research. In doing so, we identify and discuss important conceptual dimensions of goal conflict, namely, goal conflict as a cognitive construct and an experiential instance, a focus on goal interrelations or on specific goal properties, and resource versus inherent conflict, and the potential of these distinctions to further research on goal conflict. Finally, we present major challenges and pose questions that need to be addressed by future research.